Bioactive Sesquiterpene Coumarins from Ferula pseudalliacea - Dastan, Dara; Salehi, Peyman; Reza Gohari, Ahmad; Ebrahimi, Samad Nejad; Aliahmadi, Atousa; Hamburger, Matthias (Planta Medica, 2014)
One new and five known sesquiterpene coumarins were isolated from the roots of Ferula pseudalliacea. The structures were elucidated by 1D and 2D NMR, and HR-ESIMS data as 4′-hydroxy kamolonol acetate (1), kamolonol (2), szowitsiacoumarin A (3), farnesiferon B (4), farnesiferol C (5), and flabellilobin A (6). The absolute configuration of compounds 1, 2, and 4 was established by comparison of experimental and simulated electronic circular dichroism spectra using time dependence density function theory. 4′-Hydroxy kamolonol acetate and kamolonol showed antibacterial activity against Heliobacter pylori and Staphylococcus aureus at a concentration of 64 µg/mL. Kamolonol, 4′-hydroxy kamolonol acetate, and farnesiferon B displayed a cytotoxic activity in HeLa cells, with an IC50 of 3.8, 4.5, and 7.7 µM, respectively.
Keywords: Ferula pseudalliacea; Apiaceae; sesquiterpene coumarin; TDDFT; cytotoxicity; antibacterial